Marginal analysis of the effect of deficiary irrigation on the cultivation of torrontés riojano (Costos y Gestión, 2024)
In Argentina, few cost studies evaluate the impacts of irrigation on wine-growing productivity, quality and profitability. Even less relating volume, price and costs of the winegrower. This article analyzes the Cost-Volume-Profit ratio in the production of Torrontés Riojano grapes under controlled deficit irrigation (IDC) at 50% from veraison to harvest. In the Antinaco - Los Colorados Valley, La Rioja, Argentina we evaluate variations in the volume of production and quality of the grapes. Then, we determine the break-even point, margin of safety, operating leverage and perform a sensitivity study on sale prices. The results show that the IDC per hectare reduced the kilos of grapes harvested and the total costs. But, unit costs grew, negatively affecting break-even levels, security and operating leverage. The oenological quality of the grape improved, but the market maintained fixed prices. It is concluded that the IDC contributes to water savings, improves grape quality, but not profitability per hectare. This opens the discussion on profitability as an incentive to expand the cultivated area, saving water, without harming the quality of the grapes in the provincial wine sector.
Keywords: viticulture; Chilecito; wine grapes; marginal analysis